2013
DOI: 10.1002/biof.1088
|View full text |Cite
|
Sign up to set email alerts
|

DMT1 as a candidate for non‐transferrin‐bound iron uptake in the peripheral nervous system

Abstract: Iron, either in its chelated form or as holotransferrin (hTf), prevents the dedifferentiation of Schwann cells (SC), cells responsible for the myelination of the peripheral nervous system (PNS). This dedifferentiation is promoted by serum deprivation through cAMP release, PKA activation, and CREB phosphorylation. Since iron elicits its effect in a transferrin (Tf)-free environment, in this work we postulate that non-transferrin-bound iron (NTBI) uptake must be involved. Divalent metal transporter 1(DMT1) has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Furthermore, we have recently shown the presence of DMT1 in the SC plasma membrane in vivo and in vitro, which suggests its participation in cellular iron uptake. 8 DMT1 is a four-isoform protein -including two iron-responsiveelement-positive (IRE+) and two IREÀ isoforms -ubiquitously expressed at systemic and cellular levels. It is generally regarded as one of the major transport proteins for iron uptake and considered sensitive to a wide range of normal and abnormal circumstances regarding damage and adaptive mechanisms involved in recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have recently shown the presence of DMT1 in the SC plasma membrane in vivo and in vitro, which suggests its participation in cellular iron uptake. 8 DMT1 is a four-isoform protein -including two iron-responsiveelement-positive (IRE+) and two IREÀ isoforms -ubiquitously expressed at systemic and cellular levels. It is generally regarded as one of the major transport proteins for iron uptake and considered sensitive to a wide range of normal and abnormal circumstances regarding damage and adaptive mechanisms involved in recovery.…”
Section: Introductionmentioning
confidence: 99%
“…DMT1 is crucial for iron uptake and normal SC maturation DMT1 is indispensable for dietary-iron absorption in the intestine but also constitutes a crucial component of the transferrin cycle by mediating ferrous iron transport across the endosomal membrane (Gunshin et al, 2005). In the sciatic nerve, SCs show elevated levels of DMT1 in the plasma membrane as well as in the nucleus (Vivot et al, 2013), and higher DMT1 quantities were found in SCs near demyelinated lesions (Vivot et al, 2015). We have recently established that DMT1 is essential for proper oligodendrocyte maturation and is required for an efficient remyelination of the adult brain (Cheli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…DMT1 is a proton-driven metal transporter primarily responsible for iron transport from endosomes as well as for diet iron uptake in the gut (Gruenheid et al, 1995;Veuthey and Wessling-Resnick, 2014). DMT1 is expressed by neurons (Skjørringe et al, 2015), astrocytes (Erikson and Aschner, 2006;Song et al, 2007), and oligodendrocytes in the brain (Burdo et al, 2001, Cheli et al, 2018; and by SCs in the PNS (Vivot et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A very recent article indicated dimetal transporter 1 (DMT1), a Fe 2 + transporter responsible for iron uptake from the gut and transport from endosomes, as another candidate of nontransferrin bound iron (NTBI) acquisition within the PNS (151). By immunotechniques, the authors showed the presence of DMT1 in nerve homogenate, isolated from adult rat and in cultured SC, where it localizes on the plasma membrane (151).…”
Section: Iron Transport Across Bnbmentioning
confidence: 97%
“…By immunotechniques, the authors showed the presence of DMT1 in nerve homogenate, isolated from adult rat and in cultured SC, where it localizes on the plasma membrane (151). Unfortunately, they did not show any data on the specificity of the commercially available antibody used in immunofluorescence experiments, making the observation not exhaustive.…”
Section: Iron Transport Across Bnbmentioning
confidence: 97%